PHYSICO-MECHANICAL AND RELEASE PROPERTIES OF SUSTAINED RELEASE ARTESUNATE TABLETS IN HYDROXYPROPYL METHYLCELLULOSE MATRIX - Adedokun, Musiliu; Onah, Benjamin; Attama, Anthony (International Journal of Applied Pharmaceutics, 2018)
Objective: This work was aimed at formulating artesunate tablets with hydroxypropyl methylcellulose (HPMC)-a hydrophilic polymer for the purpose of achieving a sustained release profile of the drug and evaluating their properties. Methods: The solubility profile of artesunate was determined in water, methanol, ethanol, ethanol/water mixtures (50/50, 40/60 v/v), simulated intestinal fluid (SIF) without enzymes (pH 7, 7.2 and 8), simulated gastric fluid (SGF) without enzymes (pH 1.2), 0.1N hydrochloric acid (HCI), 0.1N sodium hydroxide (NaOH), 0.1N acetic acid and phosphate buffer solution, PBS (pH 7, 7.2 and 8). Four batches of oral sustained release artesunate tablets intended for once-daily dosing were formulated with 10%, 20%, 25% and 30% w/w concentrations of HPMC using wet granulation method. Evaluation of granule properties was done by determining the angle of repose, flow rate, bulk density, tapped density, Carr's index and Hausner's quotient. The compressed tablets were also evaluated using official and non-official parameters. Absolute drug contents were determined in 0.1N NaOH, ethanol and methanol. In vitro release was studied in different media and release kinetics mechanism elucidated. In vivo studies were carried out using healthy Wistar rats. Results: Artesunate was observed to exhibit solubility at varying degrees depending on solvents or media employed as well as the pH of the media. All the granule batches have Hausner's quotient value of approximately 1.2. The values for Carr's index for all the batches ranged between 30 and 40. The angle of repose, Carr's index and Hausner's quotient values indicate good flow properties of the granules for all the batches. All the tablet batches conformed to official standard in terms of weight uniformity as no single tablet deviated beyond 5% from the average weight in each batch with no significant difference in the values (p>0.05). Values of hardness increased insignificantly from batches A to D (p>0.05). Friability values were very low and follows no specific pattern among the batches but the difference in the values was significant (p<0.05). Absolute drug content reduced while in vitro release times increased as hardness increased, indicating the probable progressive reduction in the tendency of the matrix to release the drug as the concentration of HPMC increased from batches A to D. n values obtained from analysis of release mechanism were above 0.89 for each batch. Conclusion: The release mechanism was shown to be complex and the release involved zero order, first order, and Higuchi model kinetics. The biological half-life of artesunate was shown to be 1.05 hr, and metabolites which bear resemblance to artesunate in absorbance seem to be encountered. In this work, HPMC matrix yielded high-quality tablets indicating its usefulness in sustained released product development.